SARS-CoV and SARS-CoV-2 are transmitted through the air between ferrets over more than one meter distance - Kutter, Jasmin S.; de Meulder, Dennis; Bestebroer, Theo M.; Lexmond, Pascal; Mulders, Ard; Richard, Mathilde; Fouchier, Ron A. M.; Herfst, Sander (Nature communications, 2021)
SARS-CoV-2 emerged in late 2019 and caused a pandemic, whereas the closely related SARS-CoV was contained rapidly in 2003. Here, an experimental set-up is used to study transmission of SARS-CoV and SARS-CoV-2 through the air between ferrets over more than a meter distance. Both viruses cause a robust productive respiratory tract infection resulting in transmission of SARS-CoV-2 to two of four indirect recipient ferrets and SARS-CoV to all four. A control pandemic A/H1N1 influenza virus also transmits efficiently. Serological assays confirm all virus transmission events. Although the experiments do not discriminate between transmission via small aerosols, large droplets and fomites, these results demonstrate that SARS-CoV and SARS-CoV-2 can remain infectious while traveling through the air. Efficient virus transmission between ferrets is in agreement with frequent SARS-CoV-2 outbreaks in mink farms. Although the evidence for virus transmission via the air between humans under natural conditions is absent or weak for SARS-CoV and SARS-CoV-2, ferrets may represent a sensitive model to study interventions aimed at preventing virus transmission. Some epidemiological data suggests that SARS-CoV-2 can be transmitted through the air over longer distances. Here, Kutter et al. show in the ferret model that SARS-CoV-2 and SARS-CoV can be transmitted through the air over more than a meter distance, however, data should be interpreted with care, as ferrets are likely more susceptible to coronavirus infections.